Raising Dairy Herd Replacements - Dhuyvetter, Kevin C.; Harner III, Joseph P.; Brouk, Micheal (My University, 2012)
This publication discusses the decision making factors for raising dairy herd replacements.
MF399_2012_12
Keywords: MF399; Economics; Livestock; MF